John Calvin's Perspective on Church Unity and Its Implementation in Church Denominations in Ciranjang Sub-district - Harefa, Tirai Niscaya; Ndruru, Edirius; Pandie, Remegises Danial Yohanis (Institut Agama Kristen Negeri Toraja, 2024)
John Calvin viewed the unity of the church not based on church doctrine and background, but rather as one church, one faith, one God, a confession of the Apostles' faith and hope and love. The unity between churches is evident in agreements in the field of faith and Church order and in actions to unite and reconcile people in seeking solutions to social problems. The church must be united in this effort so that the Christian witness is truly authoritative. However, the development of a world that is so complex that it has resulted in the emergence of many church sects, differences in theological views, differences in understanding of the contents of the Bible, and the emergence of church egoism have become problems for uniting churches. This also happens in churches in Ciranjang, such as social friction, social jealousy, claims about the truth of the Bible, vilifying each other, considering their doctrine to be the most correct, inviting congregations to change sects, and so on. These incidents made the church seem closed and unwilling to mingle with other churches so ecumenical church programs to strengthen church unity were difficult to implement. The method used in this research is qualitative. The research results show that Calvin's concept is implemented in churches through the resilience of church leaders, congregational renewal, and restoration of relationships between churches. Unifying differences in the ecumenical movement is the key to achieving perfection in Christ the Head of the Church.